Must man be cruel? (Diametros, 2004)
Panel participants: Tadeusz Biesaga SDB, Bogdan De Barbaro, Bartłomiej Dobroczyński, Jacek Filek, Romana Kolarzowa, Andrzej Leder, Stanisław Obirek SJ, Ryszard Wiśniewski, Włodzimierz Galewicz (introductory text).